RANCANG BANGUN GAME EDUKASI BERBASIS DESKTOP UNTUK PEMBELAJARAN IPA MATERI SUMBER DAN BENTUK ENERGI DI KELAS IV SD NEGERI DANUKUSUMAN TAHUN AJARAN 2025-2026 - Taufik Hidayat, Fajar; Heru Sri Suryanti, Hera; Maria Sofia Hapsari, Alfonsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The objectives of this study were: (1) to develop a desktop-based educational game on the topic of energy sources and forms for SD Negeri Danukusuman, and (2) to determine the feasibility of using the desktop-based educational game to support the teaching of energy sources and forms at SD Negeri Danukusuman. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The educational game was developed using Construct 2 software. Data were collected through interviews, questionnaires, documentation, and Black Box Testing. The feasibility of the media was evaluated by media experts, subject matter experts, and teachers. The results showed that the desktop-based educational game was successfully developed in accordance with learning needs. Black Box Testing indicated that all game functions operated properly according to the design. The media expert validation obtained a score of 86.6%, categorized as Very Feasible, while the subject matter expert validation obtained a score of 82.5%, also categorized as Very Feasible. The teacher validation resulted in a score of 75%, which was categorized as Feasible. Therefore, the desktop-based educational game is considered feasible for assisting teachers in delivering lessons on energy sources and forms.